Integrasi WLA dan Total Expected Cost (TEC) untuk Optimalisasi Tenaga Kerja Perakitan Ridge Table di PT Romi Violeta - Muhammad Iqbal Suseno Putra; Sajiyo Sajiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Consistent production target shortfalls are a critical indicator of work system inefficiency in manufacturing. PT Romi Violeta recorded Final Assembling output for the Ridge Table product at only 95% of target on average during September–December 2025, with a cumulative deficit of 75 units. This study aimed to identify root causes through: (1) Stopwatch Time Study to establish standard time and output, (2) Work Load Analysis (WLA) to measure workload distribution across 14 operators, and (3) the IFRC questionnaire to assess fatigue levels. WLA results revealed that 5 of 14 operators were in overload condition (N > 1,10), acting as the primary assembly line bottleneck. The proposed remedy—adding 2 mobile helper workers—is projected to normalize workload distribution and guarantee stable target achievement of 7 units/day per operator with no bottleneck risk.